Faktor karakteristik dan perilaku yang berhubungan dengan on line food ordering (ofo) pada siswa SMA di Jakarta - Triyanti; Khansa Zahroosita Fatikasari; Ahmad Syafiq (MEDIA ILMU KESEHATAN, 2021)
Background: In Indonesia, prevalence of over nutrition (overweight and obesity) among children and adolescent is increasing. This can be influenced by the life style ,that is growing now, is on line food ordering (OFO).Objective: The purpose of the study are to know the description of OFO, and behavior that related with of OFO among student in SMAN 25 Jakarta. Methods: The study design was cross sectional involving 216 students. Frequency OFO is dependent variable and as independent variables are characteristic (sex, level education of parent, and pocket money), and behavior (frequency of fast food, frequency SSB, and screen time). The study methods used non-probability sampling with the sampling technique was incidental sampling. Students filled out questionnaire and submitted it by on line.Results: The results showed 38% of student used OFO with frequency of 2 times a week. Mostly students choose fast food as a menu and 26,4% students choose Sugar-Sweetened Beverages (SSB). Results of bivariate analysis showed there was relationship between level education of parent, pocket money, frequency of fast food, frequency of SSB, screen time with frequency of OFO.Conclusion: Level education of parent, pocket money, frequency of fast food, frequency of SSB, screen time with frequency of OFO related with frequency of OFO.